Pengembangan Sistem Otomatisasi Pengisian APAR: Inovasi Menuju Efisiensi dan Efektivitas - Tri Saputra, Surya; Bhima Shakti Arrafat; Supri (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
One of the fire extinguishers commonly used in various places and also utilized in practical training for students in the Aircraft Accident Rescue Program (Diploma Three) is the Portable Fire Extinguisher (APAR). In their learning, students are not only taught how to use APAR but also about its working system, maintenance, and refilling process. A drawback of the current APAR refilling process is the frequent spillage of dry chemical powder (DCP) and inaccurate measurements. The aim of this research is to design an automatic APAR refilling device that can serve as a learning tool for students. The method used is VDI 2221 (Verein Deutscher Ingenieure), a systematic approach for solving problems and optimizing the use of materials and technology. The outcome of this research is the development of a comprehensive APAR refilling device that integrates the removal of old DCP, refilling with new DCP, and nitrogen charging. The test results showed that the process of suctioning DCP powder and filling nitrogen for a 6 kg cylinder takes 7 minutes and 50 seconds. This tool makes the APAR refilling process easier, minimizes DCP spillage, and saves time during the refilling process.